Les apories des politiques inclusives. À la recherche des pratiques pédagogiques participatives : jouer pour se libérer des stigmates - Judit Vari; Vanessa Desvages-Vasselin; Émilie Dubois (Éducation et Socialisation)
In this article, we propose to test the notion of school inclusion through an investigation carried out in an adapted secondary school (which name is an EREA). Because it welcomes only students with severe academic difficulties, this school is against the current trend of inclusiveness. Indeed, in the context of our research, we understand that the EREA seems to be a protective place that would free children from their stigma, from their memories of bad pupils. Within the confines of their differences, the students testify to their feeling of letting go from the prevailing norm of the ordinary student. We seek to demonstrate that this liberation is progressive, that it is the consequence of the work and the reflection of a cohesive educational team, engaged in adapted practices of support for the students, who regularly engage with them playful activities to develop their sense of belonging to the group.